Sistem Pakar Diagnosa Penyakit Sistem Saraf Pusat dengan Metode Backward Chaining dan Certainty Factor - Felix Felix; Leo Willyanto Santoso (Jurnal Infra, 2022)
The nervous system or system is one of the smallest parts of the organs in the body, but its the most complex part. The Central Nervous System, namely brain (encephalon) and spinal cord, is the center of integration and control of all body activities so that will be very dangerous if our nervous system has problems, given that death can occur due to nervous system problems. Minimal knowledge and information make it impossible to know which disease that the nervous system is suffering from. Therefore, we need an expert who is skilled on nervous system diseases and their prevention.Based on the facts above, this final project can help us to diagnose central nervous system diseases and anticipate if someone have the disease. This application is made based on web base (PHP) and using XAMPP as MYSQL database server. In this expert system the user will choose the disease they want to diagnose first. Then, the user answers several questions related to the existing symptoms. After the user answers all the questions, the results of the diagnosis will appear along with the level of confidence and solutions that can help anticipate the disease.